OPTIMALISASI PENERIMAAN PAJAK ATAS TRANSAKSI PENGALIHAN/PENJUALAN SAHAM DAN AKSI KORPORASI PADA PERUSAHAAN TERTUTUP - Sopian, Hendri (Simposium Nasional Keuangan Negara, 2025)
Regulators that oversee share transfer/sale transactions and corporate actions for companies listed on the stock exchange (public company/Tbk.) include OJK as the supervisor, IDX as the stock exchange provider, KSEI as the central custodian and transaction settlement service provider, KPEI as the clearing and guarantee service provider for stock exchange transaction settlement, SIPF as the organiser and manager of the Investor Protection Fund. There is no regulator/third party given responsibility related to withholding/collection of tax obligations from share transfer/sale transactions and corporate actions in closed companies. The research uses a normative-empirical research method with a judicial case study approach and uses qualitative research with a descriptive analysis approach. The results show that the supervision of transfer/sale of shares and corporate actions in closed companies can be assisted by third parties such as KPPU, Notary and KemenkumHAM. The legality process (deed making, ratification and approval) cannot be done by third parties, before the tax obligations are fulfilled. With the synergy of DGT and third parties, the potential loss of tax on share transfer/sale and corporate action in a closed company can be prevented.